Assessing the Risk Factors of Cyber and Mobile Phone Bullying Victimization in a Nationally Representative Sample of Singapore Youth. (April 2016) - Holt, Thomas J.; Fitzgerald, Sarah; Bossler, Adam M.; Chee, Grace; Ng, Esther
This study utilized routine activity theory to examine the relationships between online behaviors, target suitability, and cyber and mobile phone–based bullying victimization in a nationally representative sample of youth from nine schools across Singapore. Key measures in all three categories—access to technology, online routine behaviors, and target suitability—were significant predictors of both forms of bullying victimization. In particular, females and victims of physical bullying were more likely to experience both forms of victimization. Access to technology and online routine behaviors predicted cyber and mobile phone–based bullying victimization differently. These findings demonstrate that routine activity theory is a viable framework to understand online bullying in non-Western nations, consistent with the existing literature on Western nations.